2015
DOI: 10.2337/dc14-0654
|View full text |Cite|
|
Sign up to set email alerts
|

Glycemic Variability Is Associated With Reduced Cardiac Autonomic Modulation in Women With Type 2 Diabetes

Abstract: OBJECTIVETo investigate the sex differences in cardiac autonomic modulation in patients with newly diagnosed type 2 diabetes and to determine whether cardiac autonomic modulation is associated with glycemic variability. RESEARCH DESIGN AND METHODSWe investigated a cohort consisting of 48 men and 39 women with non-insulin-treated type 2 diabetes and a known duration of diabetes <5 years. All patients were equipped with a continuous glucose monitoring sensor for 3 days, and the mean amplitude of glycemic excursi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…An explanation for the presence of CAN in recent-onset diabetes could be that HRV is impaired by early subtle glucometabolic disturbances. A recent study reported associations between glycemic variability and reduced cardiac autonomic modulation in patients with newly diagnosed and long-term type 2 diabetes (36). In line with this, nondiabetic hyperinsulinemia was associated with decreased HRV in the Atherosclerosis Risk in Communities (ARIC) study (37).…”
Section: Discussionmentioning
confidence: 61%
“…An explanation for the presence of CAN in recent-onset diabetes could be that HRV is impaired by early subtle glucometabolic disturbances. A recent study reported associations between glycemic variability and reduced cardiac autonomic modulation in patients with newly diagnosed and long-term type 2 diabetes (36). In line with this, nondiabetic hyperinsulinemia was associated with decreased HRV in the Atherosclerosis Risk in Communities (ARIC) study (37).…”
Section: Discussionmentioning
confidence: 61%
“…64,65 A reduced cardiac autonomic modulation is evident in women with T2D with high GV. 66 There is also considerable interest for the emerging association between GV and the decline of cognitive function. 67,68 HbA1c variability appears to predict symptoms of depression in elderly individuals with T2D, 69 including the risk of developing the Alzheimer disease.…”
Section: Glucose Variability: Hard Outcomes In Persons With and Withomentioning
confidence: 99%
“…Although direct research that evaluated the association between hormone variability and the development of cancer was not published, hormonal disturbance may be served as the mediator between development of cancer and glycemic variability. The association between glycemic variability and hormonal disturbance was previously reported, even though it is still in controversy whether change of hormone may cause glycemic disturbance [34,35], or vice versa [36]. In terms of the association between variability in hormone and cancer, it was also previously reported [37].…”
Section: Discussionmentioning
confidence: 92%